Fraction of exhaled nitric oxide is higher in liver transplant recipients than in controls from the general population: a cohort study - Arentoft, Nicoline S.; Fialla, Annette D.; Krohn, Paul S.; Patursson, Magda T.; Thudium, Rebekka F.; Suarez-Zdunek, Moises A.; Høgh, Julie; Lauridsen, Emilie H. E.; Hansen, Jesper B.; Jensen, Jens-Ulrik S.; Perch, Michael; Møller, Dina L.; et al. (Frontiers in Immunology, 2024)
Background: Fraction of exhaled nitric oxide with an expiratory flow of 50 ml/s (FENO50) is a biomarker of eosinophilic airway inflammation. Liver transplant recipients have an increased risk of pulmonary infections, but little is known about the burden of chronic pulmonary diseases in this group. We aimed to assess the prevalence of elevated FENO50 in liver transplant recipients and compare it to controls from the general population. Methods: FENO50 was measured in 271 liver transplant recipients from The Danish Comorbidity in Liver Transplant Recipients (DACOLT) study and 1018 age- and sex-matched controls from The Copenhagen General Population Study (CGPS). Elevated FENO50 was defined as ≥25 or ≥50 parts per billion (ppb). Analyses were adjusted for known and suspected confounders. Results: The median age of liver transplant recipients was 55 years (interquartile range (IQR) 46-64), and 58% were men. Liver transplant recipients had higher median FENO50 than controls (16 ppb [IQR 10-26] vs. 13 ppb [IQR 8-18.], p<0.001). Furthermore, liver transplant recipients had a higher prevalence of elevated FENO50 (for FENO50 ≥25 ppb 27% vs 11%, p<0.001 and ≥50 ppb 4% vs 2%, p=0.02). Results were similar after adjusting for age, sex, smoking status, use of airway medication, and blood eosinophil counts (adjusted odds ratio [OR] for FENO50 ≥25 ppb 3.58 [95% CI 2.50-5.15, p<0.0001], adjusted OR for FENO50 ≥50 ppb 3.14 [95% CI 1.37-7.20, p=0.007]). Conclusion: Liver transplant recipients had elevated FENO50, implying increased eosinophilic airway inflammation. The clinical impact of this finding needs further investigation.